Comparison of Five Level and Seven Level Inverter Based Static Compensator System - G. Ramya; V. Ganapathy (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The STATCOM is one of the shunt type FACTS controllers which can supply reactive power and improve bus voltage. STATCOM has advantages like transient free switching and smooth variation of reactive power. This paper deals with the comparison of five level and seven level based STATCOM systems. Usually DC output from the PV source is amplified using a single boost converter. The output of the boost converter is applied to the multilevel inverter system. The ability of STATCOM to improve the receiving end voltage is analyzed using the proposed boost converter. The performance of five level and seven level STATCOM systems are compared in terms of THD and receiving end voltage